2017
DOI: 10.1186/s12906-017-1871-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a herbal extract powder (YY-312) from Imperata cylindrica Beauvois, Citrus unshiu Markovich, and Evodia officinalis Dode on body fat mass in overweight adults: a 12-week, randomized, double-blind, placebo-controlled, parallel-group clinical trial

Abstract: BackgroundYY-312 is a herbal extract powder from Imperata cylindrica Beauvois, Citrus unshiu Markovich, and Evodia officinalis Dode, which have health promoting effects, including body fat reduction. We aimed to evaluate the efficacy and safety of YY-312 for body fat reduction in overweight adults.MethodsThis was a 12-week, randomized, double-blind, placebo-controlled, parallel-group clinical trial performed in overweight Korean adults aged 19–60 years with a body mass index of 25.0–29.9 kg/m2. The daily dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 26 publications
0
44
0
2
Order By: Relevance
“…−1 kg vs −2.7 kg); BFM (−1.6 kg), BF% (−1.5%) and WC were also significantly decreased Cho et al, 2017aCho et al, ,2017b NA-No data available for the body weight at the end of the treatment period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…−1 kg vs −2.7 kg); BFM (−1.6 kg), BF% (−1.5%) and WC were also significantly decreased Cho et al, 2017aCho et al, ,2017b NA-No data available for the body weight at the end of the treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidences that the green tea extracts are effective in reducing body weight in these recently published RCTs were mostly inconclusive (Dostal et al, 2016a(Dostal et al, , 2016bSamavat et al, 2016). Within the studied herbal preparations in the selected RTCs Aster spathulifolius extract (Cho et al, 2016) and a combination containing Imperata cylindrica Beauvois, Citrus unshiu Markovich, and Evodia officinalis Dode (Cho et al, 2017b) were the only exceptions that achieved weight reduction greater that 3% from initial weight within 12 weeks, but with very small number of participants included.…”
Section: Clinical Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Bitter orange extracts' efficacy in inducing weight loss has been shown in some clinical studies [147,148], and literature revisions including studies conducted on subjects who received products containing p-synephrine alone or in combination with other supplements concluded that the consumption of this dietary supplement is overall safe and may induce modest weight loss [149,150]. The most recent review, involving approximately 30 human studies and over 600 subjects, have confirmed that evidences supporting the anti-obesogenic role of bitter orange extracts are limited and uncertain, as they are often studied in combination with other molecules.…”
Section: Bitter Orangementioning
confidence: 98%